PENERAPAN METODE INDIVIDUAL SYSTEM DALAM MENINGKATKAN MINAT BACA ANAK USIA 5-6 TAHUN DI BIMBA AIUEO - Lestari, Sri; Dewi, Ratna Sari; Sutarjo, Sutarjo (Comm-Edu (Community Education Journal), 2025)
Reading interest is an essential foundation for literacy development that should be nurtured from early childhood. Its growth is strongly determined by learning methods that are in harmony with children’s characteristics, needs, and pace of learning. This study explores the application of the Individual System method in fostering reading interest among children aged 5–6 years at biMBA AIUEO Walahar Karawang. Employing a qualitative descriptive approach, the research involved one administrator, three motivators, and three parents as key informants. Data were collected through interviews, observations, and documentation, and subsequently analyzed through stages of reduction, presentation, and conclusion drawing. The findings reveal that the Individual System was implemented through several structured steps: conducting non-academic initial assessments, preparing gradual learning modules based on the Small Step System, applying person-to-person learning, and conducting narrative evaluations with parental involvement. This method was strengthened by diverse learning media and the establishment of positive emotional bonds between motivators and children. The outcomes indicate improvements in cognitive abilities, sustained enthusiasm for reading, and enhanced fine motor skills. Overall, the Individual System emerges as a holistic and enjoyable pedagogical approach that effectively nurtures reading interest in early childhood education.